Consulting a traditional healer and negative illness perceptions are associated with non‐adherence to treatment in Indonesian women with breast cancer. Issue 10 (24th March 2014) - Iskandarsyah, Aulia; de Klerk, Cora; Suardi, Dradjat R.; Sadarjoen, Sawitri S.; Passchier, Jan
Abstract Objective The aim of the present study was to test the association between psychosocial factors and delay in uptake of treatment and treatment non‐adherence in Indonesian women with breast cancer. Methods Seventy consecutive patients with breast cancer who were treated at the Hasan Sadikin Hospital in Indonesia were recruited. They completed a demographic form, the non‐adherence questionnaire, the Breast Cancer Knowledge Test, the Brief Illness Perception Questionnaire, the Multidimensional Health Locus of Control Scales, the Satisfaction with Cancer Information Profile and the Distress Thermometer. Results Seventeen (24%) out of 70 patients reported that they had delayed initiating treatment at the hospital, and nine (13%) out of 70 patients had missed two or more consecutive treatment sessions. In the bivariate analyses, we found no significant differences on any of the psychological variables between patients who delayed initiating treatment and those patients who did not, whereas patients who had missed two or more consecutive sessions had lower satisfaction with the type and timing of information provided and more negative illness perceptions than patients who had not missed their sessions. In multivariate regression analyses, consulting a traditional healer before diagnosis was associated with treatment delay (β = 1.27, p = 0.04). More negative illness perceptions (β = 0.10, p = 0.02) and whether a traditional healer had been consulted after diagnosis (β = 1.67, p = 0.03) were associated with missing treatment sessions. Conclusions Indonesian health professionals need to be aware of patients' negative illness perceptions and their unrealistic belief in traditional healers. Copyright © 2014 John Wiley & Sons, Ltd.